Changes in the Relationship Between Gray Matter, Functional Parameters, and Quality of Life in Patients with a Post-Stroke Spastic Upper Limb After Single-Event Multilevel Surgery: Six-Month Results from a Randomized Trial - Patricia Hurtado-Olmo; Pedro Hernández-Cortés; Ángela González-Santos; Lourdes Zuñiga-Gómez; Laura Del Olmo-Iruela; Andrés Catena (Diagnostics)
Introduction: Advanced magnetic resonance imaging (MRI) techniques in neuroplasticity evaluations provide important information on stroke disease and the underlying mechanisms of neuronal recovery. It has been observed that gray matter density or volume in brain regions closely related to motor function can be a valuable indicator of the response to treatment. Objective: To compare structural MRI-evaluated gray matter volume changes in patients with post-stroke upper limb spasticity for >1 year between those undergoing surgery and those treated with botulinum toxin A (BoNT-A) and to relate these findings to upper limb function and quality of life outcomes. Materials and Methods: Design. A two-arm controlled and randomized clinical trial in patients with post-stroke upper limb spasticity. Participants. Thirty post-stroke patients with spastic upper limbs. Intervention. Participants were randomly assigned (1:1 allocation ratio) for surgery (experimental group) or treatment with BoNT-A (control group). Main outcome measures. The functional parameters were analyzed with Fugl-Meyer, Zancolli, Keenan, House, Ashworth, pain visual analogue, and hospital anxiety and depression scales. Quality of life was evaluated using SF-36 and Newcastle stroke-specific quality of life scales. The carer burden questionnaire was also applied. Clinical examinations and MRI scans were performed at baseline and at six months post-intervention. Correlations between brain volume/thickness and predictors of interest were examined across evaluations and groups. Results: Five patients were excluded due to the presence of intracranial implants. Eleven patients were excluded from analyses since they were late dropouts. Changes were observed in the experimental group but not in the control group. Between baseline and six months, gray matter volume was augmented at the hippocampus and gyrus rectus and cortical thickness was increased at the frontal pole, occipital gyrus, and insular cortex, indicating anatomical changes in key areas related to motor and behavioral adaptation These changes were significantly related to subjective pain, Ashworth spasticity scale, and Newcastle quality of life scores, and marginally related to the carer burden score. Conclusions: The structural analysis of gray matter by MRI revealed differences in patients with post-stroke sequelae undergoing different therapies. Gray matter volume and cortical thickness measurements showed significant improvements in the surgery group but not in the BoNT-A group. Volume was increased in areas associated with motor and sensory functions, suggesting a neuroprotective or regenerative effect of upper limb surgery.